PERANAN KEPEMIMPINAN DALAM PEMBANGUNAN FISIK DI DESA KULO KECAMATAN KULO KABUPATEN SIDENRENG - Megaria Megaria; Hariyanti Hamid; Andi Astinah Adnan (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
the village of Kulo, Kulo District, Sidenreng Rappang Regency 2. Factors that influence the leadership role of the village head in physical development in the Kulo Village, Kulo District, Sidenreng Rappang Regency.Descriptive quantitative research methods. The population of the research is the entire community of Kulo Village, Kulo District, amounting to 3039 people, the determination of the sample using a random sample, with the sample in this study is 97 people.The results showed that the variable (x) the leadership role of the village head was 49.67% of the unfavorable category produced while the expected 100. Likewise for the final data results on both variables indicate that the role of leadership of the village head in physical development in the Village of Kulo, Kulo District, Sidenreng Rappang Regency is 50% categorized as not good. Factors influencing the leadership role of village heads in Kulo Village, Kulo District, Sidenreng Rappang Regency are: Human resources (7%), Sources of funds (21%), Community participation (29%).